INOVASI MANAJEMEN KUALITAS MELALUI KOLABORASI STAKEHOLDER DI SD NEGERI 011 SAMARINDA SEBERANG - Rahmita, Siti Rahmita; Bahrani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe quality management innovation through stakeholder collaboration at SD Negeri 011 Samarinda Seberang. The research method used was qualitative with a case study approach, where data were collected through in-depth interviews, observation, and document analysis. The research subjects included principals, teachers, staff, parents, and community representatives. The results showed that stakeholder collaboration has increased active participation in the quality management process, with the level of participation in evaluation meetings becoming more enthusiastic. In addition, the quality of the learning process has improved thanks to resource support and collaboration programs such as “Smart Class” and “Teacher and Parent Workshop”. Student learning outcomes have also shown significant improvement, with the average semester exam score rising from 70 to 80. School resource management has become more effective thanks to financial and material contributions from stakeholders, while a strong and inclusive culture of collaboration has been created through initiatives such as the “Cerdas Mandiri Committee” and the “Education Discussion Forum”. The findings support the Total Quality Management (TQM) theory that emphasizes the importance of stakeholder collaboration in improving education quality. The study recommends developing a stakeholder collaboration model that can be adopted by other schools, as well as increasing stakeholders' active participation through supportive programs and policies. Thus, stakeholder collaboration is proven as an effective strategy to improve quality management in primary schools.